LANGUAGE UNIVERSALS AND UNIVERSAL INPUT CONDITIONS (SIUSANA KWELDJU) - Maulizan ZA (Getsempena English Education Journal, 2015)
This essay discusses about human language, human have the common system in their language. The same system of the languages is called as Language Universals. it can be assumed that Language Universals or known as Linguistic Universals is a pattern that occurs systematically across natural languages.